New Twists of 3D Chiral Metamaterials. Issue 26 (21st February 2019) - Fernandez‐Corbaton, I.; Rockstuhl, C.; Ziemke, P.; Gumbsch, P.; Albiez, A.; Schwaiger, R.; Frenzel, T.; Kadic, M.; Wegener, M.
Abstract: Rationally designed artificial materials, called metamaterials, allow for tailoring effective material properties beyond ("meta") the properties of their bulk ingredient materials. This statement is especially true for chiral metamaterials, as unlocking certain degrees of freedom necessarily requires broken centrosymmetry. While the field of chiral electromagnetic/optical metamaterials has become rather mature, the field of elastic/mechanical metamaterials is just emerging and wide open. This research news reviews recent theoretical and experimental progress concerning 3D chiral mechanical and optical metamaterials, with special emphasis on work performed at KIT. Abstract : Chiral optical and mechanical 3D rationally designed artificial materials, called metamaterials, give access to new effective material degrees of freedom. The similarities and differences between optics and mechanics in regard to chiral continuum descriptions and the experimental and theoretical status of the two subfields are reviewed. Furthermore, future perspectives and potential applications are outlined.